Outbreak investigation steps in the case of 2019 novel coronavirus infection, a review - Dessalew Habte Alene; Waktole Yadeta (Annals of Antivirals and Antiretrovirals - Peertechz Publications, 2020)
Coronaviruses are a large family of viruses that are common in many different species of animals, including camels, cattle, cats, birds and bats. In January 2020, it causes an outbreak of respiratory illness caused by a novel (new) coronavirus first identified in Wuhan, Hubei Province, China. Additional cases have been identified in a growing number of other international locations, including the United States. Most coronaviruses spread the same way other cold-causing viruses do: through infected people coughing and sneezing, by touching an infected person's hands. The clinical signs displayed from infected patients include runny or stuffy nose, coughing, sore throat, and sometimes a fever. There are no vaccines or antiviral drugs that are approved for prevention or treatment. Scientists were able to isolate a strain of the new coronavirus quickly, with the genetic sequence being made available for laboratories across the world to independently develop PCR tests that can confirm infection in a person. It can be investigated mainly by following outbreak investigation steps, health education, restriction of movement around the outbreak zone and contingency preparedness plans. There are ongoing investigations to learn more. Within short period of time following its outbreak, the 2019-nCoV causes high number of people's death and huge international economic loss associated with health, trade and transportation.  The aim of this paper is to understand the cause, identify methods for investigating or controlling it and to prevent any future occurrences.